2008
DOI: 10.4049/jimmunol.181.11.8036
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Lung CD8 T Cell Oligoclonal Expansions upon Smoking Cessation in a Mouse Model of Cigarette Smoke-Induced Emphysema

Abstract: The role of adaptive immunity in the development or progression of chronic obstructive pulmonary disease (COPD) remains undefined. Recently, the presence of autoantibodies and autoreactive T cells has been demonstrated in COPD patients. In addition, oligoclonal expansions of lung T cells have been observed in COPD patients, but the overlapping incidence of infections, tumors, and cigarette smoke exposure obscures the antigenic stimulus. We analyzed the TCR V␤ repertoire of CD4 and CD8 T cells purified from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 42 publications
3
62
1
1
Order By: Relevance
“…Oligoclonal CD8 + T cell infiltrates are present in both the lungs of COPD patients and also in mice chronically exposed to cigarette smoke, where they persist even after a sustained period of smoking cessation (32,33). Furthermore, a number of groups have demonstrated that CD8 + T cell infiltration is positively correlated with airflow limitation and disease progression (31,34).…”
Section: T Cellsmentioning
confidence: 99%
“…Oligoclonal CD8 + T cell infiltrates are present in both the lungs of COPD patients and also in mice chronically exposed to cigarette smoke, where they persist even after a sustained period of smoking cessation (32,33). Furthermore, a number of groups have demonstrated that CD8 + T cell infiltration is positively correlated with airflow limitation and disease progression (31,34).…”
Section: T Cellsmentioning
confidence: 99%
“…Bitransgenic Ccsp-rtta 3 (tetO) 7 -CMV-Raet1a (FVB/NJ background, henceforth referred to as Raet1a-tg mice) mice were generated as described (6,25). Raet1a-tg mice conditionally express Raet1a on the alveolar and airway epithelium in a doxycycline (DOX)-inducible manner (6,25).…”
Section: Micementioning
confidence: 99%
“…Lungs were perfused with 6 ml 13 PBS containing 0.6 mM EDTA. Lungs were withdrawn aseptically from the chest cavity, and leukocytes were isolated in a manner previously described (7). Spleen leukocytes were prepared by gently pressing spleens through a 100-mm cell strainer in 5 ml RPMI 1640.…”
Section: Lung and Spleen Leukocyte Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Within 1 week of smoking cessation, there is a partial normalization of MMP-2 and MMP-9 levels in BAL fluid (Seagrave et al, 2004), though lymphocyte abnormalities including CD8 T cell oligoclonal expansions persist (Seagrave et al, 2004;Motz et al, 2008). It is likely that the combination of altered inflammatory response and cytokine profiles are responsible for the variations between strains in structural and functional measures of emphysema as well as for the reparative response seen upon smoking cessation.…”
Section: The Development Of Emphysema Is Mouse Strain Dependentmentioning
confidence: 99%